Perancangan Special Occasion Wear Terinspirasi dari Kebaya Encim dengan Teknik 3D Embellishment - Davis, Vanessa Angeline; Enrico, Enrico; Githapradana, Dewa Made Weda (MODA, 2024)
In the past, kebaya was worn by women from different ethnicities. Kebaya encim is one of Indonesian women’s many traditional clothing that was influenced by Peranakan culture. However, the rise of practical culture and changing human lifestyles have led to the perception that kebaya encim is less modern, too vibrant, and not very comfortable. The lack of frequency and enthusiasm among the younger generations in wearing kebaya encim has driven development steps resulting in modern special occasion wear inspired by kebaya encim. This design is carried out using primary and secondary data research methods. Primary data is obtained through interviews with experts and extreme users and through direct observations on embroidery techniques. Secondary data is obtained from various sources such as scientific publications, books, journals, and dissertations. This design process uses the design thinking technique to create a solution for designing five modern kebaya garments using decoratove 3D fabric and embroidery embellishments. The motifs used in the designs are developments from classic floral kebaya encim motifs such as lilies, orchids, chrysanthemums, jasmine, and others. The target market for this design is women aged 20-35 years. Testing is conducted after creating product prototypes to get feedback and suggestions from the respondents before proceeding to further development. The results of this design process are expected to repopularize and develop kebaya encim as part of Indonesia’s intangible cultural heritage.